Artificial Nesting Structures for the Double-Crested Cormorant - Meier, Thomas I. (University of Wisconsin-Stevens Point, College of Natural Resources, 1980)
Natural nesting habitat for the double-crested cormorant (Phalacrocorax auritus), consisting of flooded dead timber, has become limited in the midwest portion of the United States. Population trends have followed this decline in habitat and today the species is classified as endangered in Wisconsin. Artificial nesting structures, consisting of a pole with platforms, proved to be a successful substitute for natural nest sites on the George W. Mead Wildlife Area in central Wisconsin and thus provided an excellent method for rehabilitating deteriorating natural rookeries. Three platform types were tested in 1974. Platform Type-A had a chicken wire surface, Platform Type-B a lath surface, and Platform Type-C a box surface. Platform Type-B proved to be most successful and with minor modification was used almost exclusively for platform construction in 1975 and 1976. Cormorant use of the modified Platform Type-B was high in comparison to all others tested and it is recommended for further rookery restoration projects. Artificial structures, poles with attached platforms, are constructed of treated wood and have a life expectancy of 45 years. Platform use at the Mead rookery increased from 25.6% in 1974 to 57.5% in 1976 as deterioration of natural nest sites within the rookery accelerated. Production of fledged young per nest averaged 1.94 and 2.16 for nests in natural nest sites and artificial platforms respectively. Use of artificial platforms by the great blue heron (Ardea heroidias) was documented each year of the study. A total of 3.8, 2.3, and 9.4% of all heron nests constructed in the rookery were in artificial platforms for 1974, 1975, and 1976, respectively. Production averaged 2.2 young per nest. Artificial structures should be placed within 25-ft of natural nesting trees; platforms should be placed within the vertical height interval occupied by natural nests; platforms should be spaced 3-ft apart vertically for cormorants and 4-ft apart for herons; and consecutive platforms should be placed in 180° vertical rotation. Perching structures were also erected to provide perching sites in excessively deteriorated areas of the rookery. Total construction costs were $125.00 per 4 platform structures and $200.00 per 6 platform structures. Total construction cost per perching structure was $97.75.